Feasibility of Cognitive Training in Combination With Transcranial Direct Current Stimulation in a Home-Based Context (TrainStim-Home): study protocol for a randomised controlled trial. Issue 6 (10th June 2022) - Thams, Friederike; Rocke, Merle; Malinowski, Robert; Nowak, Rafal; Grittner, Ulrike; Antonenko, Daria; Flöel, Agnes
Abstract : Introduction: With the worldwide increase of life expectancy leading to a higher proportion of older adults experiencing age-associated deterioration of cognitive abilities, the development of effective and widely accessible prevention and therapeutic measures has become a priority and challenge for modern medicine. Combined interventions of cognitive training and transcranial direct current stimulation (tDCS) have shown promising results for counteracting age-associated cognitive decline. However, access to clinical centres for repeated sessions is challenging, particularly in rural areas and for older adults with reduced mobility, and lack of clinical personnel and hospital space prevents extended interventions in larger cohorts. A home-based and remotely supervised application of tDCS would make the treatment more accessible for participants and relieve clinical resources. So far, studies assessing feasibility of combined interventions with a focus on cognition in a home-based setting are rare. With this study, we aim to provide evidence for the feasibility and the effects of a multisession home-based cognitive training in combination with tDCS on cognitive functions of healthy older adults. Methods and analysis: The TrainStim-Home trial is a monocentric, randomised, double-blind, placebo-controlled study. Thirty healthy participants, aged 60–80 years, will receive 2 weeks of combined cognitive training and anodal tDCS over left dorsolateral prefrontal cortex (target intervention), compared with cognitive training plus sham stimulation. The cognitive training will comprise a letter updating task, and the participants will be stimulated for 20 min with 1.5 mA. The intervention sessions will take place at the participants' home, and primary outcome will be the feasibility, operationalised by two-thirds successfully completed sessions per participant. Additionally, performance in the training task and an untrained task will be analysed. Ethics and dissemination: Ethical approval was granted by the ethics committee of the University Medicine Greifswald. Results will be available through publications in peer-reviewed journals and presentations at national and international conferences. Trial registration number: NCT04817124 .